Analisis Hukum Penggunaan Tenaga Kerja Asing Terhadap Pertumbuhan Ekonomi Di Kota Medan - Fani Budi Kartika; Erni Darmayanti (Jurnal Ilmiah Penegakan Hukum, 2021)
In line with the movement and development of globalization which encourages the movement of capital flows to all corners of the world, then there is also a fairly large movement of population or labor between countries. This is a factor that the owners of capital certainly need skilled workers who can manage their investment in the destination country. This study aims to analyze and provide the basic concept of implementing the protection of the Manpower Act Number 13 of 2003 for foreign workers in Medan City and to analyze whether the use of foreign workers in Medan City has an effect on economic growth or on the contrary has an impact on economic decline and reduced employment opportunities for local workers in Medan City. This research uses normative and doctrinal research, which is a descriptive qualitative research. The results of this study are that in Law No. 13 of 2003 concerning Manpower, the regulation on the use of foreign workers is contained in Chapter VIII, Article 42 to Article 49. And there is an effect of the use of foreign workers in Medan on the increase in the economy of Medan City